MODELS OF MUSLIM PERSONALITY IN CONTEXT OF SUFISM IN DAGHESTAN (17TH - 19TH CENTURIES) - Sihaliev, Samil' Sihalievic (History, Archeology and Ethnography of the Caucasus, 2024)
This article examines how the history of Sufism in Daghestan might be written through the prism of time-specific behavioral models that characterize the ideal type of Muslim. Based on the analysis of a large number of manuscripts in private and public collections, four main models can be distinguished between the 17th and 19th centuries. The first of them is characterized by a deep immersion in ethical norms in conjunction with rituals. The second model paid close attention to issues of esotericism and occult knowledge. Third model, while not being Sufi, is nevertheless considered in this article, as it is focused on rejection of Sufism as a behavioral model and is focused on legal theory. The fourth model, which is also Sufi, is characterized by a great emphasis on the Sufi ritual practice. All these three models did not supplant one another, but coexisted in certain historical periods. This pluralism of models determined the variety of behavioral stereotypes of Daghestani Muslims, who defined themselves through correlation or adherence to one or another. Despite the difference in these behavioral models, they still each define in their own way what it means to be an ideal Muslim.
Keywords: Daghestan; Sufism; rationalism; behavioral model; ideal Muslim